Kompatibilitas Agama (Islam) dengan HAM - Mua’allim, Amir (Unisia, 2016)
The problem of human rights denotes a fundamental issue because its relation with the interest of human life as whole. Human rights depart from Islam view point is the emergencies (darury) that declares should be understood by every body. In the term of Islamic perspective to understand and to practice the human rights principles can be regarded as the obligation for every person individually. The cases that declared by the institutions for example the National Commission For Human Rights Affairs (Komnas HAM) and the like, the essence is equal to the principles of Islamic teaching. To solve the problems of human rights according to Islam, Muslim scholars should interpret the tenet of Islam not only by using textual approach but also contextual approach that combine with the historical approach.